Enhancing management of technology and innovation for sustainable competitiveness of SMEs - Hoang, Dinh Phi (2016)
Being impacted by the financial and economic crises and the threats of economic downturn spiral, social unrest and environmental pollutions…, businesses and people are talking a lot about sustainable development as a target, a desire and an aspiration of human beings in the 21st century. In many countries, small and medium enterprises (SMEs) hold a large number and play a very important role in the sustainable development. How to build and develop sustainable competitiveness for SMEs still remains an unanswered question for many governments. This paper introduces a new approach and a basic tool that SMEs can apply to build sustainable competitiveness in the context of global cooperation, competition, and integration.